Tools for Sustainable Development of Regional Energy Systems - Gitelman, Lazar D.; Dobrodey, Vladimir V.; Kozhevnikov, Mikhail V. (Economy of Regions, 2020)
Nowadays, it is relevant to consider changes in the structure of the fuel and energy balance of industrial regions and the availability of imported fuel and energy resources, especially in the areas that lack energy sources. The ongoing structural shifts in energy consumption systems and the growing uncertainty in energy markets encourage the development of tools for improving the sustainable development of regional energy systems. To refine the theoretical and methodological basis of the study, we defined its conceptual framework, described the differences between sustainable functioning and development of the energy sector and determined the factors of its regional differentiation and manifestations of the energy crisis. Further, we identified the shortcomings of the existing methods for forecasting the demand for electricity. We paid special attention to quality factors of strategic planning in the region, in particular, the used statistics and documents. Based on the analysis of integrated resource planning (IRP) methodology, our experience in forecasting fuel and energy balances, assessment of sectoral indicators of energy efficiency and energy demand in the region, we proposed a model for predictive and analytical justification of regional programmes for energy development. Such a model significantly increases the information reliability of these programmes’ implementation. Considering organisational tools to support sustainable development, we developed a regional energy management scheme and a mechanism stimulating local energy companies to improve energy efficiency in the consumption sector, enhance regional competition and attract investments in the renewal of fixed assets. The study has practical significance due to recommendations and tools for adjusting regional energy policy based on the coordination of the predicted parameters for various participants in the energy supply process.